Documentación y evolución de componentes reusables : Contratos de reuso con semántica de comportamiento - Giandini, Roxana Silvia (2002)
At the present, software developers are confronted to constant changes in the market. Due to this, they need obtaining flexible and customizable components to attend the changing nature of the applications. Using this kind ofcomponents in application construction can result expensive even with proper documentation. The documentation quality is basically important in the evolution phase. In reusable components documentation, most complex problems appear due to the abstract constitution of the design.